2022
DOI: 10.3390/foods11071037
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Risk Assessment of Bacillus cereus Growth during the Warming of Thawed Pasteurized Human Banked Milk Using a Predictive Mathematical Model

Abstract: Bacillus cereus is relatively resistant to pasteurization. We assessed the risk of B. cereus growth during warming and subsequent storage of pasteurized banked milk (PBM) in the warmed state using a predictive mathematical model. Holder pasteurization followed by storage below −18 °C was used. Temperature maps, water activity values, and B. cereus growth in artificially inoculated PBM were obtained during a simulation of manipulation of PBM after its release from a Human Milk Bank. As a real risk level, we cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Demazeau et al has noted the effectiveness of the high pressure of 350 MPa on B. cereus spores [2]. The long-term experience of Human Milk Banks [49] as well as the results of our previous studies [5,6] showed that pasteurized milk safety can be achieved if routine post-pasteurization evaluation is performed and if samples (bottles) with positive microbiological findings are discarded. The total discard rate due to microbial positivity in our 5-year follow-up ranged between 8 and 10%, with spore-forming microbes accounting for almost 72% of all positive findings [5].…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Demazeau et al has noted the effectiveness of the high pressure of 350 MPa on B. cereus spores [2]. The long-term experience of Human Milk Banks [49] as well as the results of our previous studies [5,6] showed that pasteurized milk safety can be achieved if routine post-pasteurization evaluation is performed and if samples (bottles) with positive microbiological findings are discarded. The total discard rate due to microbial positivity in our 5-year follow-up ranged between 8 and 10%, with spore-forming microbes accounting for almost 72% of all positive findings [5].…”
Section: Discussionmentioning
confidence: 73%
“…Despite the high discard rate, the amount of milk delivered annually from our bank is sufficient to cover the needs of Pediatric Intensive Care Units [5,6]. However, the discard rate has prevented the use of banked milk for a broader range of newborns, including healthy babies that cannot be breast-fed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, B . cereus endospores may not completely be eliminated by pasteurization and can therefore give rise to new vegetative forms of B. cereus in the milk post-pasteurization [1] . Additionally, several reports show that pasteurized human milk can be contaminated with Bacillus cereus [2] [4] .…”
Section: Introductionmentioning
confidence: 99%